AI-Augmented Mobile ESG Data Capture: A Conceptual Framework for Sustainable Procurement in Engineering and Construction - Michael Torti , Ikechukwu; Chaudhary, Niyati; Jamil Alotoum, Firas (International Journal of Interactive Mobile Technologies (iJIM), 2026)
The importance of environmental, social, and governance (ESG) in the procurement process of the engineering and construction industry cannot be overemphasized. However, supplier ESG reporting is still done in a traditional manner. This paper introduces a conceptual model that combines mobile-based data capture and analytics of artificial intelligence (AI) to support sustainability in construction and engineering. Digital technologies are the main devices for the real-time capture of ESG data in supplier ecosystems. The model demonstrates how managers, AI supporting them, can obtain ESG dashboards to enhance supplier selection, compliance with the procurement’s sustainability criteria, and rational decision-making. Practical examples from the cement and steel supply chains are provided. The author’s contribution stems from presenting the model in theory and practice, where its use brings ESG integration into the procurement processes in sustainable, transparent, and scalable supply chains.